Relationship between human capital management and organisational performance: an empirical evidence from select Indian banks. (2016) - Vihari, Nitin Simha; Singh, Bindu; Rao, M.K.
In a dynamic business environment, identifying the most efficient and effective business practice which could sustain the growth prospects of an organisation has been a great challenge. In the light of it, the present study highlights the opportunity of leveraging the organisation's human capital potential to endow with rapid reaction to turbulent environment and enhance performance. This research investigates the impact of HCM drivers on the organisational performance and also attempts to measure the human capital management (HCM) maturity level index, using a sample of 372 respondents from the select Indian public sector banks. Partial least squares structural equation modelling (PLS-SEM) was adopted in order to test the hypotheses. Findings and implications of the study are discussed, along with the limitations and future research avenues.